2014
DOI: 10.1074/jbc.m113.534313
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Tyrosine 247 Inhibits Protein Kinase G-1α Activity by Attenuating Cyclic Guanosine Monophosphate Binding

Abstract: Background: PKG-1␣ nitration plays an important role in the development of pulmonary hypertension. Results: We identified Tyr 247 as the key residue susceptible to nitration and inhibition of PKG-1␣. Conclusion: Nitration attenuates PKG activity by reducing its affinity for cGMP. Significance: Preventing the nitration of PKG-1␣ could prevent the phenotypic remodeling in the blood vessels during the development of a number of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…In another study, it has been shown that nitration of tyrosine 247 in PKG-1α results in decreased cGMP binding and thereby decreased PKG activity in pulmonary artery smooth muscle cells (12). Tyrosine nitration of PKG has also been shown to occur in ovine fetal intrapulmonary veins in a hypoxia-dependent manner that is endothelial NOS (eNOS)-independent but through increased levels of nitrite and nitrate (10).…”
Section: Molecular Mechanisms Of Nitrative Stress In the Pathogenementioning
confidence: 99%
See 2 more Smart Citations
“…In another study, it has been shown that nitration of tyrosine 247 in PKG-1α results in decreased cGMP binding and thereby decreased PKG activity in pulmonary artery smooth muscle cells (12). Tyrosine nitration of PKG has also been shown to occur in ovine fetal intrapulmonary veins in a hypoxia-dependent manner that is endothelial NOS (eNOS)-independent but through increased levels of nitrite and nitrate (10).…”
Section: Molecular Mechanisms Of Nitrative Stress In the Pathogenementioning
confidence: 99%
“…Prominent tyrosine nitration, a hallmark of nitrative stress, is evident in lung tissues of severe PH patients including IPAH patients (13). Increased tyrosine nitration of PKG, for instance, is observed in lung tissues of IPAH patients (12). The activity of eNOS is markedly increased in the lungs of IPAH patients compared with healthy controls, without significant change in its protein levels (11).…”
Section: Nitrative Stress In Pulmonary Hypertension Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also show that nitration at tyrosine 247 attenuates PKG-Ia activity. An antibody against 3-NT-Y247 identifies increased levels of nitrated PKG-Ia in humans with PH (57,58). Interestingly, although cGMP is considered the sole vasoactive molecule generated by sGC, a recent study reveals that hypoxia may promote sGC to synthesize a vasoconstrictor inosine 39, 59-cyclic monophosphate.…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%
“…Although in Shunt lambs increased BNP-mediated activation of particulate GC may be able to compensate [81]. In addition, although it does not appear to be chaperoned by hsp90, the target of cGMP, protein kinase G-1α (PKG-1α) is also compromised in Shunt lambs [82] through the nitration of Y247 that reduces the ability of the protein to bind cGMP [83] (Figure 3). Thus, in addition to an increase in NO generation the downstream effectors of NO are also compromised.…”
Section: Hsp90 and No Signalingmentioning
confidence: 99%